Application of Mild Therapeutic Hypothermia on Stroke: A Systematic Review and Meta-Analysis - Shaheen E. Lakhan; Fabricio Pamplona (Stroke Research and Treatment)
Background. Stroke occurs due to an interruption in cerebral blood supply affecting neuronal function. Body temperature on hospital admission is an important predictor of clinical outcome. Therapeutic hypothermia is promising in clinical settings for stroke neuroprotection. Methods. MEDLINE/PubMed, CENTRAL, Stroke Center, and ClinicalTrials.gov were systematically searched for hypothermia intervention induced by external or endovascular cooling for acute stroke. NIH Stroke Scale (NIHSS) and modified Rankin Scale (mRS) were the main stroke scales used, and mortality was also reported. A meta-analysis was carried out on stroke severity and mortality. Results. Seven parallel-controlled clinical trials were included in the meta-analysis. Sample sizes ranged from 18 to 62 patients, yielding a total of 288. Target temperature (~33°C) was reached within 3-4 hours. Stroke severity (Cohen's 𝑑=−0.17, 95% CI: −0.42 to 0.08, 𝑃=0.32; I2 = 73%; Chi2 = 21.89, 𝑃=0.0001) and mortality (RR=1.60, 95% CI: 0.93 to 2.78, 𝑃=0.11; I2 = 0%; Chi2 = 2.88, 𝑃=0.72) were not significantly affected by hypothermia. Discussion. Hypothermia does not significantly improve stroke severity; however, this finding should be taken with caution due to the high heterogeneity and limited number of included studies. No impact on mortality was observed.